The Effect of Organizational Trust and Job Satisfaction on Job Performance with Employee Engagement as a Mediating Variable - Nabilla, Maulidya; Budiono, Budiono; Witjaksono, Andre Dwijanto; Wardoyo, Dewie Tri Wijayati (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The purpose of this study was to examine and analyze the effect of organizational trust and job satisfaction on job performance through employee engagement at PT. Adikara Jaya Sentosa. This research is a causality study with a quantitative approach. The sampling technique uses a saturated sample with a total of 75 respondents. The statistical analysis used in this study is the partial least squares (PLS) with the help of smartPLS 3.0 software. The results of this study prove that organizational trust has a positive and significant effect on job performance. Organizational trust has a positive and significant effect on employee engagement. Job satisfaction has a positive and significant effect on job performance. Job satisfaction has a positive and significant effect on employee engagement. In the indirect effect analysis, employee engagement is able to mediate the influence between organizational trust and job satisfaction on job performance.